EBV‐positive mucocutaneous ulcer arising in rheumatoid arthritis patients treated with methotrexate: Single center series of nine cases. Issue 1 (7th January 2019) - Satou, Akira; Banno, Shogo; Hanamura, Ichiro; Takahashi, Emiko; Takahara, Taishi; Nobata, Hironobu; Katsuno, Takayuki; Takami, Akiyoshi; Ito, Yasuhiko; Ueda, Ryuzo; Nakamura, Shigeo; Tsuzuki, Toyonori
Abstract : Methotrexate (MTX) is currently used as first‐line anchor drug for rheumatoid arthritis (RA). Therefore, the number of MTX‐associated lymphoproliferative disorders, including Epstein–Barr virus‐positive mucocutaneous ulcer (EBVMCU), has increased. Some aspects of MTX‐associated EBVMCU (MTX‐EBVMCU), particularly clinical behavior and treatment for RA after MTX cessation, have not been well described. Herein, we report nine cases of MTX‐EBVMCU with clinical information regarding RA. Seven of nine patients showed spontaneous regression (SR) after immunosuppressive (IS) cessation. The other two required cytotoxic chemotherapy. Eventually, all achieved complete remission. No patients experienced EBVMCU relapse. Eight patients had RA flare after IS cessation. To control the RA activity, rituximab was administered to three patients. The remaining patients were treated by other agents. Regarding the RA activity, all were in the status of low disease activity or clinical remission. In conclusion, MTX‐associated EBVMCU has an indolent clinical course and SR after IS cessation can be expected. After the withdrawal of MTX, the majority of patients experience RA flare and required treatment. In our series, RA was well controlled without reinitiating MTX. Therefore, to prevent the EBVMCU relapse, it might be advisable to avoid MTX reintroduction, and rituximab might be the more preferable agent for RA treatment.